Melvin Beederman, superhero : Terror in tights - Trine, Greg.; Montijo, Rhode (New York : Henry Holt, 2007)
When Los Angeles superhero Melvin Beederman starts receiving mysterious, threatening emails, he and Candace, his partner in uncrime, must figure out who is out to get him and then do something about it.
610L
Decoding demand: 85 (very high) Semantic demand: 98 (very high) Syntactic demand: 82 (very high) Structure demand: 86 (very high)
Accelerated Reader AR
Keywords: Heroes -- Fiction; Humorous stories; Los Angeles (Calif.) -- Fiction; Fiction